2004
DOI: 10.1111/j.1944-9720.2004.tb02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Literary Texts and Grammar Instruction: Revisiting the Inductive Presentation

Abstract: This article outlines an approach to explicit grammar instruction that uses literary texts as comprehensible, meaning‐bearing input. In this approach, which employs strategies from the teaching of grammar and the teaching of reading, literary texts serve as the basis of the inductive presentation of new grammatical forms and as a springboard for communicative practice of these forms after explicit instruction. The goal is to provide learners with meaning‐bearing input to assist their acquisition of grammatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It is beyond the scope of this article to address the historical and ideological roots behind this separation (Davis, 2000) or to propose major changes in how literature faculty conduct their courses. Furthermore, we will not address the use of authentic literary texts in the beginning language classroom (e.g., Katz, 2002; Paesani, 2005; Schultz, 1995; Shook, 1996). Instead, our research examines the advanced undergraduate literature course as a venue for form‐focused instruction by examining the ways in which literature professors do or do not attend to problems of linguistic form.…”
mentioning
confidence: 99%
“…It is beyond the scope of this article to address the historical and ideological roots behind this separation (Davis, 2000) or to propose major changes in how literature faculty conduct their courses. Furthermore, we will not address the use of authentic literary texts in the beginning language classroom (e.g., Katz, 2002; Paesani, 2005; Schultz, 1995; Shook, 1996). Instead, our research examines the advanced undergraduate literature course as a venue for form‐focused instruction by examining the ways in which literature professors do or do not attend to problems of linguistic form.…”
mentioning
confidence: 99%
“…Mandatory proficiency testing with minimum requirements to take literature courses might work as a gatekeeping tool but would probably greatly reduce the number of students who could take the literature classes. As discussed in the literature (e.g., Paesani, 2005; Schultz, 1995; Shook, 1996), introducing authentic and literary texts into 100‐ through 300‐level classes is another option. Given the difficulty that students in the current study had with the literature they read, earlier exposure to literary texts might help facilitate the transition to 400‐level literature courses.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pedagogical articles have been published offering recommendations for working with authentic literary texts in beginning‐ and intermediate‐level courses (cf. Adair‐Hauck & Donato, 2002; Bueno, 2002; Katz, 2002; Paesani, 2005; Scott & Huntington, 2007). Major educational institutions have taken steps to integrate language, literature, and culture in their curricula; examples include French at the University of California, Berkeley (Schultz, 1995), and German at Georgetown (Byrnes & Kord, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is suitable for beginners of the target language as it acts as a stepping stone in preparing students to deal with the authentic text. Therefore, it can be concluded that this approach can be employed in assisting students to get a better understanding of the text (Mishan, 2005;Nunan, 2006;Paesani, 2005). Activities for this approach could include the teacher telling the story or a poem using simpler language, the use of translation using other mother tongues and reading paraphrased versions or notes provided in the workbook or by the teacher (Chien, Yunus, & Mohamad, 2008).…”
Section: Teaching Approaches Used To Teach Literature In Language Clamentioning
confidence: 99%